Evidence for the decay B0→[omega,omega] and search for B0→[omega,phi] - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2014)
We describe searches for B meson decays to the charmless vector-vector final states ωω and ωϕ with 471×106B¯B pairs produced in e+e− annihilation at √s=10.58 GeV using the BABAR detector at the PEP-II collider at the SLAC National Accelerator Laboratory. We measure the branching fraction B(B0→ωω)=(1.2±0.3+0.3−0.2)×10−6, where the first uncertainty is statistical and the second is systematic, corresponding to a significance of 4.4 standard deviations. We also determine the upper limit B(B0→ωϕ)<0.7×10−6 at 90% confidence level. These measurements provide the first evidence for the decay B0→ωω, and an improvement of the upper limit for the decay B0→ωϕ.